Design, manipulability analysis and optimization of an index finger exoskeleton for stroke rehabilitation. (January 2022) - Li, Guotao; Cheng, Long; Sun, Ning
Abstract: Rehabilitation medicine studies have indicated that occupational therapy has a positive effect on the recovery of hand function. However, few wearable hand exoskeletons can assist in performing the adduction and abduction exercises of occupational therapy. Therefore, the wearable index finger rehabilitation exoskeleton (WIFRE) is studied in this paper. First, a WIFRE is proposed to realize the index joint's independent actuation, including adduction and abduction movements. Second, the local/global kinematic and dynamic manipulability measures are proposed and analyzed to evaluate the performance of the WIFRE. The analysis results show that the dimensional parameters of the WIFRE have a significant effect on its global manipulability measures. The global kinematic and dynamic manipulability measures can be improved by 13%–15% compared with the corresponding minimums. Third, a multi-parameter multi-objective optimization method is proposed to simultaneously enhance the three global manipulability measures. Finally, experiments are performed to verify the effectiveness of the index finger exoskeleton and the global manipulability measures. Highlights: A wearable index finger rehabilitation exoskeleton (WIFRE) is proposed. Effects of dimensional parameters of the WIFRE on the manipulability are obtained. A multi-objective optimization method for the WIFRE is proposed.